Traditions of Indian music - Gowri Kuppuswamy; Hariharan M (New Delhi: B R Rhythms, 2017)
With particular reference to India.
"Earlier published with the title "An anthology of Indian music"--Title page verso.
Keywords: Music Carnatic; Music India; Music; Arts